Mechanism Of Pore Water Pressure And Groundwater Fluctuation In Slope Stability Under Heavy Rainfall Condition - Zulmahdi, Zuraini (Universiti Sains Malaysia, 2022)
In this study, physical-based model was used in this work to identify the influence of excessive rainfall intensity on the stability of a slope. Mining sand from a mining region in Kampung Kuala Trong, Taiping, Perak, is the soil used in the physical modelling. The parameter of the soil that lead to slope failure are characterized. Selected extreme rainfall intensity is based on direct adoption. From the identified rainfall intensity, Volumetric Water Content and Matric Suction can be measured using the physical model. The simulation is conducted in a 2 different cases and parameter. The duration of the simulated rainfall is 6-hour. The overall trend of the matric suction measurement in each case is increasing with a few exceptions of tensiometer that shows decreasing value. After the rain simulation stopped, the matric suction decreased rapidly and remain stagnant follow by a significant dropping significantly. For the volumetric water content, there is a similar increase in the trend during the rainfall simulation. However, there is difference in term of initial and increment of water content for different part of the slope. for the lower part of the slope, the initial water content is much higher which at 24 - 26 % and during the rainfall simulation it increase up to 30 - 33 %. While for the upper part are at 20 -22 % with a slight increment during the rainfall simulation which is increase to 23 - 26 %. For all cases there is no failure had been occurred but there are still have slightly soil movement of the slope. Numerical analysis is done to model the cases in GeoStudio software. To see the factor of safety and it shows that the increased in rainfall intensity would affect the factor of safety of the slope stability.